Systematic review of well-being interventions for minority healthcare workers - Bafna, Tanvi; Malik, Mansoor; Choudhury, Mohua C.; Hu, William; Weston, Christine M.; Weeks, Kristina R.; Connors, Cheryl; Burhanullah, M. Haroon; Everly, George; Michtalik, Henry J.; Wu, Albert W. (Frontiers in Medicine, 2025)
IntroductionHealthcare workers’ well-being is of utmost importance given persistent high rates of burnout, which also affects quality of care. Minority healthcare workers (MHCW) face unique challenges including structural racism and discrimination. There is limited data on interventions addressing the psychological well-being of MHCW. Thus, this systematic review aims to identify interventions specifically designed to support MHCW well-being, and to compare measures of well-being between minority and non-minority healthcare workers.MethodsWe searched multiple electronic databases. Two independent reviewers conducted literature screening and extraction. The Mixed Methods Assessment Tool (MMAT) or Joanna Briggs Institute (JBI) criteria were utilized to assess the methodological quality of studies, based on the study design. Total scores as percentages of criteria met were used to determine overall quality as low (<40%), moderate (40-80%), or high (>80%). For conflicts, consensus was reached through discussion. Meta-analysis was not possible due to heterogeneity of study designs.ResultsA total of 3,816 records were screened and 43 were included in the review. The majority of included studies (76.7%) were of moderate quality. There were no randomized control trials and only one study included a well-being intervention designed specifically for MHCW. Most (67.4%) were quantitative-descriptive studies that compared well-being measures between minority and non-minority identifying healthcare workers. Common themes identified were burnout, job retention, job satisfaction, discrimination, and diversity. There were conflicting results regarding burnout rates in MHCW vs non-minority workers with some studies citing protective resilience and lower burnout while others reported greater burnout due to compounding systemic factors.DiscussionOur findings illuminate a lack of MHCW-specific well-being programs. The conflicting findings of MHCW well-being do not eliminate the need for supports among this population. Given the distinct experiences of MHCW, the development of policies surrounding diversity and inclusion, mental health services, and cultural competency should be considered. Understanding the barriers faced by MHCW can improve both well-being among the healthcare workforce and patient care.